Ent-11α-Hydroxy-15-oxo-kaur-16-en-19-oic-acid Inhibits Growth of Human Lung Cancer A549 Cells by Arresting Cell Cycle and Triggering Apoptosis - Li, Li; Chen, George G; Lu, Ying-nian; Liu, Yi; Wu, Ke-feng; Gong, Xian-ling; Gou, Zhan-ping; Li, Ming-yue; Liang, Nian-ci (Chinese Journal of Cancer Research; Vol 24, No 2 (June 29, 2012): Chinese of Journal Cancer Research, 2012)
Objective: To examine the apoptotic effect of ent-11α-hydroxy-15-oxo-kaur-16-en-19-oic-acid (5F), a compound isolated from Pteris semipinnata L (PsL), in human lung cancer A549 cells. Methods: A549 cells were treated with 5F (0–80 μg/ml) for different time periods. Cytotoxicity was examined using a MTT method. Cell cycle was examined using propidium iodide staining. Apoptosis was examined using Hoechst 33258 staining, enzyme-linked immunosorbent assay (ELISA) and caspase-3 activity analysis. Expression of representative apoptosis-related proteins was evaluated by Western blot analysis. Reactive oxygen species (ROS) level was measured using standard protocols. Potential interaction of 5F with cisplatin was also examined. Results: 5F inhibited the proliferation of A549 cells in a concentration- and time-dependent manner. 5F increased the accumulation of cells in sub-G1 phase and arrested the cells in the G2 phase. Exposure to 5F induced morphological changes and DNA fragmentation that are characteristic of apoptosis. The expression of p21 was increased. 5F exposure also increased Bax expression, release of cytochrome c and apoptosis inducing factor (AIF), and activation of caspase-3. 5F significantly sensitized the cells to cisplatin toxicity. Interestingly, treatment with 5F did not increase ROS, but reduced ROS production induced by cisplatin. Conclusion: 5F could inhibit the proliferation of A549 cells by arresting the cells in G2 phase and by inducing mitochondrial-mediated apoptosis.